Tanggapan Masyarakat Kota Bandung terhadap Program Penyiaran Dakwah Cahaya Qalbu di Radio X FM Bandung - Sulton Arif Mauludi; M. Rachmat Effendi; Nandang HMZ (UNISBA Press, 2021)
Abstract. This research is about da'wah broadcast programs that have been done by many previous researchers. However, there is no research that examines the public's response to a da'wah broadcasting program with the object of the Bandung city community. On that basis, this research focuses on